Assessment of Sex Differences in Recovery of Motor and Sensory Impairments Poststroke. (August 2020) - Hawe, Rachel L.; Cluff, Tyler; Dowlatshahi, Dar; Hill, Michael D.; Dukelow, Sean P.
Background . Understanding potential sex differences in stroke recovery is important for prognosis, ensuring appropriate allocation of health care resources, and for stratification in research studies. Previously, functional measures have shown poorer outcomes for females, however, little is known about sex differences that may exist in specific motor and sensory impairments. Objective . The aim of this study was to utilize robotic assessments of motor and sensory impairments to determine if there are sex differences at the impairment level in stroke recovery over the first 6 months poststroke. Methods . We used robotic and clinical assessments of motor and sensory impairments at 1, 6, 12, and 26 weeks poststroke in 108 males and 52 females. Linear mixed models were used to examine the effect of sex on recovery poststroke, controlling for age and lesion volume. Results. In general, we did not find significant sex differences across a range of assessments. The exception to this was a sex × age interaction for the Purdue Pegboard Assessment, where we found that females had better performance than males at younger ages (<62 years), but males had better performance at older ages. Conclusions . While recruitment biases need to be acknowledged when generalizing our results to stroke recovery at-large, our results suggest that sex differences do not exist at the impairment level poststroke.